Footplate releasing technique for correcting short noses in revision and Asian rhinoplasty - Alp A.; YENİGÜN A.; ÖZTURAN O. (My University, 2026)
Background: To achieve aesthetically pleasing results that are in harmony with the face, it is essential that the nose length is proportionate to facial proportions. Short and upturned noses can give the impression that the tip of the nose has been cut off when viewed from the front. Objective: The aim of this study is to obtain a longer nose by increasing the prominence of the nasal tip through repositioning the medial and lateral crura using the Footplate Releasing Technique in patients with short noses, particularly in Asian patients. Materials and Methods: The Footplate Releasing Technique was applied to 37 revision cases and 32 primary Asian noses. The technique consists of three stages. In the first stage, the medial crus was cut from the nasal base. Then, the lateral crus was lengthened by stealing from the medial crus. In the final stage, the cut and shortened medial crura were sutured to a strong columellar strut placed between them and extended to the nasal floor. Patients were followed up for an average of 12 months (range: 6-18 months). Results: The Footplate Releasing Technique was successfully applied to 37 revision cases and 32 primary Asian noses. The nasal tip point was recreated at the desired level with extended lateral crura. The nasal tip was moved forward and downward, reducing cephalic rotation while achieving the desired projection. Targeted tip point, rotation, and projection results were obtained in all paConclusions: In revision cases and short nose deformities commonly seen in Asian patients, the Footplate Releasing Technique the overall nasal structure. (c) 2025 The Author(s). Published by Elsevier Ltd on behalf of Surgeons. This is an open access article under the CC BY-NC-ND
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Cerrahi; Klinik Tıp; Klinik Tıp (Med); Surgery; Clinical Medicine; Clinical Medicine (Med)